World Bank Research Digest, Vol. 8(2) - World Bank (Washington, DC, 2014)
This Research Digest newsletter includes the following headings: Shared prosperity and the mitigation of poverty; The simple algebra of the shared prosperity indicator; The global income distribution: 1988 - 2008; Narrowing the gap in India; Is workfare really cost-effective?; Growth still is good for the poor; and What is the effect of growth on the distribution of opportunities?